2020
DOI: 10.1039/c9cp06474e
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Volmer–Heyrovský mechanism of hydrogen evolution on a nitrogen doped carbon nanotube: constrained molecular dynamics versus the nudged elastic band method

Abstract: This study presents the first direct simulation of the hydrogen evolution reaction using a fully explicit, dynamic DFT approach and highlights the importance of incorporating solvent dynamics in the rigorous description of electrochemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 86 publications
0
54
0
Order By: Relevance
“…This allows an efficient mapping of the electrode potential dependence of the key kinetic quantities. 14 Importantly, while the charge extrapolation requires only a single reaction path simulation in contrast to the above briefly discussed methods, special attention should be given to the accurate calculation of the electrode potential and appropriate choice of charge partitioning scheme.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows an efficient mapping of the electrode potential dependence of the key kinetic quantities. 14 Importantly, while the charge extrapolation requires only a single reaction path simulation in contrast to the above briefly discussed methods, special attention should be given to the accurate calculation of the electrode potential and appropriate choice of charge partitioning scheme.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…reaction barriers. 14,17 Moreover, the fluctuating interfacial solvent and formation of the electrochemical double-layer (EDL) structure require considerable statistical sampling over extended simulation times to appropriately represent the microscopic details of the electrified solid−liquid interface. 18,19 Platinum constitutes arguably the best performing electrode material for several electrocatalyzed reactions, including the hydrogen evolution reaction (HER), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We opted against the use of an explicit solvation model since developing reliable solvation shells would require ab initio molecular dynamics simulations. 68 Performing these simulations would be computationally unfeasible owing to the large number of considered solvents and the partially large size of the solvent molecules. Considering the errors associated with the SMD solvation model, 62 the use on an implicit solvation model is expected to be only slightly less accurate than using a computationally much more expensive explicit solvation shell.…”
Section: Computational Detailsmentioning
confidence: 99%
“…While the rigorous theoretical treatment of the GCE-TST has only recently been demonstrated, the formalism has already found use in fixed potential DFT studies of electrocatalytic reactions in static environments [64][65][66]266,[272][273][274][275] using a constant potential modification of the NEB method. 276 Also, calculations with dynamical solvent have been performed 277,278 using the blue moon ensemble 279 method. Pioneering studies have shown the importance of analyzing the kinetics at constant potential rather than constant particle number as well as demonstrated the viability of GCE-TST in computing electrocatalytic rate constants from first principles for a wide class of electrocatalytic PCET reactions such as for hydrogen evolution, 64,65,272,275 CO 2 reduction, 266,280 CO reduction, 281 NH 3 oxidation, 282 nitrogen reduction, 283 and oxygen reduction reactions, 277 for example.…”
Section: Adiabatic Reactionsmentioning
confidence: 99%